2023
DOI: 10.1088/1361-6560/acebb1
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing image blurring of PROPELLER MRI via untrained method

Abstract: Objective: Periodically Rotated Overlapping ParallEL Lines with Enhanced Reconstruction (PROPELLER) used in magnetic resonance imaging (MRI) is inherently insensitive to motion artifacts but with an expense of around 60% increase in minimum scan time. An untrained deep learning method is proposed to accelerate PROPELLER MRI while suppressing image blurring. 
Approach: Several reconstruction methods have been developed to accelerate PROPELLER with reduced sampling on blades. However, image quality is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, improvements have been made to accelerate dynamic imaging by utilizing UNN regularized by spoiled gradient echo (SPGR) (Slavkova et al 2023). Sequentially, leveraging UNN to generalize the degradation process of blurred images provides a solid foundation and also demonstrates the insensitivity of UNN to distribution shifts (Saju et al 2023), which can be viewed as the characterization of image low-level statistical priors through a parameterized convolutional neural network. Our earlier study has also already demonstrated the feasibility of UNN in representing physical information, including the latent images and approximations of CSM (Liu et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, improvements have been made to accelerate dynamic imaging by utilizing UNN regularized by spoiled gradient echo (SPGR) (Slavkova et al 2023). Sequentially, leveraging UNN to generalize the degradation process of blurred images provides a solid foundation and also demonstrates the insensitivity of UNN to distribution shifts (Saju et al 2023), which can be viewed as the characterization of image low-level statistical priors through a parameterized convolutional neural network. Our earlier study has also already demonstrated the feasibility of UNN in representing physical information, including the latent images and approximations of CSM (Liu et al 2023).…”
Section: Introductionmentioning
confidence: 99%